2006
DOI: 10.1002/cyto.a.20222
|View full text |Cite
|
Sign up to set email alerts
|

A new method to quantify phagocytosis and intracellular degradation using green fluorescent protein‐labeled Escherichia coli: Comparison of cord blood macrophages and peripheral blood macrophages of healthy adults

Abstract: Interactions between innate and adaptive immune functions in neonatal macrophages (MΦ) are still unclear. We therefore established a method to quantify bacterial phagocytosis and intracellular degradation, using green fluorescent protein (GFP)‐labeled Escherichia coli in combination with phenotypic analysis. The kinetics of the proportion of phagocyting MΦ, phagocytosed bacteria per MΦ, and bacterial degradation were comparable for cord blood MΦ of term neonates and MΦ of healthy adults. Phenotyping revealed C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 11 publications
5
55
0
Order By: Relevance
“…The phagocytosis assay was carried out as previously described (38). Incubation was performed for 60 min at a multiplicity of infection of 50:1.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…The phagocytosis assay was carried out as previously described (38). Incubation was performed for 60 min at a multiplicity of infection of 50:1.…”
Section: Phagocytosis Assaymentioning
confidence: 99%
“…Articles neonates have reported diminished (14), enhanced (12,13), or equivalent capability (11,13). These inconsistent findings are likely to reflect methodological differences, as sample type (e.g., purified cells or whole blood), preparations and species of bacteria, together with the use of humoral factors (e.g., complement) vary considerably between studies (11).…”
Section: Phagocytosis In Newborn Whole Bloodmentioning
confidence: 99%
“…However, the data, particularly for deficiencies in phagocytosis, are inconsistent (11). There are no definitive comparisons of phagocytosis between adults and neonates; studies have identified positive (12,13), negative (14), and neutral (11,13) trends in functionality between the groups (15). Similarly, the reported correlation between GA and phagocytosis functionality is inconsistent (12,16).…”
mentioning
confidence: 99%
“…PBMCs and CBMCs were isolated by density gradient centrifugation (Biochrom AG, Berlin, Germany) as described (18). Washed cells were resuspended in VLE RPMI-1640 (Biochrom) containing 10% heat-inactivated fetal calf serum (Biochrom) at 2 × 10 6 cells/ml in flat-bottom 24 well cell culture plates (Costar, Bodenheim, Germany).…”
Section: Cell Culturesmentioning
confidence: 99%
“…Although phagocytic activity and intracellular degradation of bacteria did not differ in comparison with those of monocytes from peripheral blood of adults (PBMOs) (17,18), PICD was greatly diminished in CBMOs (19).…”
mentioning
confidence: 95%